Oxford new syllabus mathematics workbook 3 - Ban Har, Yeap (Karachi: Oxford University Press., 2024)
Oxford New Syllabus Mathematics Workbook 3 is a supplementary resource designed to reinforce and enhance students' understanding of the advanced mathematical concepts introduced in Oxford New Syllabus Mathematics 3. The workbook offers a variety of exercises covering topics such as algebra, geometry, trigonometry, mensuration, and statistics. Through structured practice and problem-solving activities, it helps students solidify their grasp of theoretical concepts while promoting analytical thinking and application to real-world problems. This workbook is an essential tool for building confidence and mastery in preparation for more advanced mathematical studies.